Style icons fashion - Contemporary Arts Media (Firm) (South Melbourne, Vic. : Contemporary Arts Media, 2005)
Interviews with some of the top designers from the United Kingdom, United States, Italy, France, and Australia
Keywords: Costume design -- 20th century; Fashion designers -- Interviews; Fashion